Fundamental Principles of Risk Management in Restructuring, Reorganization, and Liquidation of Non-Profit and Profit-Oriented Companies - Deni Sunaryo; Dhany Isnaeni Darmawan; Anisya Dwi Wulandari Kaya; Melynda Anggraini; Melda Dwi Rahma (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The implementation of financial risk management policies and principles is a critical aspect of managing the banking sector, non-profit organizations, and business environments in Indonesia. The adoption of International Financial Reporting Standards (IFRS) has significantly altered accounting practices in Indonesia, yielding both opportunities and challenges for companies. Furthermore, credit restructuring, encapsulated in the